2018
DOI: 10.1111/birt.12359
|View full text |Cite
|
Sign up to set email alerts
|

Trends in rooming‐in practices among hospitals in the United States, 2007‐2015

Abstract: Background Rooming-in, or keeping mothers and infants together throughout the birth hospitalization, increases breastfeeding initiation and duration, and is one of the Ten Steps to Successful Breastfeeding. Methods The Centers for Disease Control and Prevention’s (CDC) Maternity Practices in Infant Nutrition and Care (mPINC) survey is a biennial census of all birth facilities in the United States and its territories. Data from the 2007–2015 mPINC surveys were used to assess trends in the prevalence of hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…Our data confirm that rooming-in has a strong facilitating effect on exclusive breastfeeding [ 39 , 40 , 41 , 42 ]. Instead, and in contrast to previous reports [ 21 , 43 , 44 ], attendance to birth preparation courses did not appear to have a statistically significant positive effect.…”
Section: Discussionsupporting
confidence: 83%
“…Our data confirm that rooming-in has a strong facilitating effect on exclusive breastfeeding [ 39 , 40 , 41 , 42 ]. Instead, and in contrast to previous reports [ 21 , 43 , 44 ], attendance to birth preparation courses did not appear to have a statistically significant positive effect.…”
Section: Discussionsupporting
confidence: 83%
“…It is reported that rooming-in increases breastfeeding initiation [35][36][37], but the effects of rooming-in on breastfeeding remain uncertain [38,39]. In our experience, rooming-in is not capable of causing an increase in breastfeeding by itself.…”
Section: Discussioncontrasting
confidence: 59%
“…In our population, more than half of the mothers attended prenatal classes and almost all of them knew the UNICEF/WHO definition of roomingin. Nevertheless, consistently with previous data published in the literature (26), less than half of them continuously practiced it. Previous studies have noted a similar discrepancy between knowledge and practice, which results in a suboptimal application of the information provided (27,28).…”
Section: Discussionsupporting
confidence: 83%